Association Between Endocrine Markers, Accumulated Workload, and Fitness Parameters During a Season in Elite Young Soccer Players - Nobari, Hadi; Mainer-Pardos, Elena; Adsuar, José Carmelo; Franco-García, Juan Manuel; Rojo-Ramos, Jorge; Cossio-Bolaños, Marco Antonio; Urzua Alul, Luis; Pérez-Gómez, Jorge (Frontiers in Psychology, 2021)
The purposes of this study were to analyze differences between endocrine markers in soccer players, based on playing positions, and the correlations between endocrine markers (testosterone, cortisol, growth hor-mone, and insulin-like growth factor-1), with accumulated workload training and fitness parameters (maxi-mal oxygen uptake (V̇O2max), countermovement jump (CMJ), isometric maximal strength (1-RM) of the knee for hamstring (ISH) and quadriceps (ISQ) muscles) during early-, mid-, and end-season. Twenty-four elite soccer players under-17 participated in this study. The results showed that there was no difference between levels of the endocrine markers among the different positions of the players. Significant correlations were observed between endocrines parameters and fitness performance (ISQ, ISH, VO2max and CMJ). Regression analysis showed that 1-RM and VO2max were the best predictor of endocrine markers. These findings demonstrated that activity profiles of youth soccer players were not influenced by endocrine markers. Also, it may be assumed that endocrines levels can be used to better explain physical capacities of this population. Finally, endocrines markers may help to predict changes in 1-RM and V̇O2max.